2013
DOI: 10.1155/2013/681439
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Precancerous Lesions of Upper Gastrointestinal Tract: From the Endoscopists' Viewpoint

Abstract: Upper gastrointestinal tract cancers are one of the most important leading causes of cancer death worldwide. Diagnosis at late stages always brings about poor outcome of these malignancies. The early detection of precancerous or early cancerous lesions of gastrointestinal tract is therefore of utmost importance to improve the overall outcome and maintain a good quality of life of patients. The desire of endoscopists to visualize the invisibles under conventional white-light endoscopy has accelerated the advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 127 publications
(183 reference statements)
0
17
0
Order By: Relevance
“…Image‐enhanced endoscopy, which includes equipment and dye‐based techniques, has been proposed as a better screening tool than conventional white‐light imaging (WLI) endoscopy for gastrointestinal tract cancers . Several different methods for image‐enhanced endoscopy have been applied to esophageal cancer screening, and among them, the narrow band imaging (NBI) system and Lugol chromoendoscopy are well known and efficient in the detection of malignancies of the squamous cell epithelium . The characteristics of neovascularization and the depletion of intracellular glycogen during the cancerization of the squamous epithelium lead to brownish discoloration and white‐pink unstained malignant mucosa under NBI and Lugol chromoendoscopy, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Image‐enhanced endoscopy, which includes equipment and dye‐based techniques, has been proposed as a better screening tool than conventional white‐light imaging (WLI) endoscopy for gastrointestinal tract cancers . Several different methods for image‐enhanced endoscopy have been applied to esophageal cancer screening, and among them, the narrow band imaging (NBI) system and Lugol chromoendoscopy are well known and efficient in the detection of malignancies of the squamous cell epithelium . The characteristics of neovascularization and the depletion of intracellular glycogen during the cancerization of the squamous epithelium lead to brownish discoloration and white‐pink unstained malignant mucosa under NBI and Lugol chromoendoscopy, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed promising results regarding a transfer of this imaging method to the area of the head and neck with a sufficient differentiation of pathological lesions to physiological tissue in the upper gastrointestinal tract like pharynx, larynx and the esophagus [3, 2426]. Furthermore, preliminary results regarding CLE examinations in the oral cavity showed potentials for detecting cancerous lesions even in their early forms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preliminary results regarding CLE examinations in the oral cavity showed potentials for detecting cancerous lesions even in their early forms. However, these studies were mainly performed either with an experimental set-up, in ex vivo settings, on animal models or with fluorescent agents not suitable for a routine clinical investigation [3, 13, 1922, 2426]. …”
Section: Discussionmentioning
confidence: 99%
“…3,9,21 Gastrointestinal endoscopy must be done regularly and consists of esophagogastroduodenoscopy, colonoscopy and enteroscopy with Chromo-endoscopy staining (blue methylen, indigocarmine, Lugol) or Narrow band imaging technique (NBI) or endo-microscopy examinations. Histopathology examination is an important examination that should be performed to diagnose the presence of precancerous lesions.…”
Section: Supporting Examinationmentioning
confidence: 99%
“…[26][27][28] Examination with high sensitivity and specificity close to 100% to diagnose precancerous lesion/ cancer are esophagogastroduodenoscopy examination, colonoscopy, enteroscopy, Chromo-endoscopy and confocal laser endomicroscopy with biopsy examination and histopathology examination. 21,29 These supporting examinations must be performed periodically to monitor the progress of precancerous lesions.…”
Section: Managementmentioning
confidence: 99%